$20,000 Lure to Bring Pans Out for Las' Lap - Unknown (Sunday Express)
Berger Paints Trinidad Limited announced plans to revive Las' Lap in Port-of-Spain with a steelband competition on Carnival Tuesday. Selwyn Drayton, Berger's General Manager stated that the company will be awarding a total of $20,000 in prizes for the best beating steelband, the best beating pan-round-the-neck band and the first band to reach the roundabout.
Keywords: Corporate sponsorship -- Trinidad and Tobago; Steel bands (Music) -- Trinidad and Tobago; Steel band music -- Trinidad and Tobago; Steel bands (Music) -- Competitions -- Trinidad and Tobago